Free-living nematodes in Sarawak coastal waters - Shabdin, Mohd Long; Norliana, Rosli; Cheng, Ann Chen (Penerbit UMT, 2013)
The taxonomic study on free-living nematodes had been carried out in Sarawak coastal waters to clarify the systematic and distribution of nematodes in Sarawak. This is the first taxonomic study conducted in Sarawak. A total of one hundred and eleven (111) species, representing forty seven (47) genera and twenty (20) families were identified from twenty four study sites along the Sarawak coastal waters. All species are first recorded in Sarawak, and were grouped according to their habitat (sediment type) of the station under study. All species were described and illustrated with detailed taxonomic notes and discussions. Pictorial keys of identification for species were also produced.